Redescription of Bonatitan reigi (Sauropoda: Titanosauria), from the Campanian–Maastrichtian of the Río Negro Province (Argentina) - Salgado, Leonardo (2014)
The titanosaur sauropod Bonatitan reigi is redescribed. The material collected, originally interpreted as pertaining to two different individuals, is reorganised in five individuals, and the original type specimen is separated into three different individuals. One of the braincases is designated as a new type specimen. Some materials are described by the first time (sacral ribs, distal caudal, chevrons, metacarpals, astragalus and metatarsals), others reinterpreted as different bones (‘ulna’ and ‘radius’). The diagnosis of B. reigi is emended, removing some of the original characters (longitudinal groove located on the suture between the parietals that continues posteriorly over the supraoccipital to the foramen magnum) and adding some new (small paired pits on the frontals and posterior ridge of the metacarpal IV). The phylogenetic analysis does not support B. reigi as a member of the Saltasaurinae, but rather as a basal member of a broad clade of sauropods that in turn is recovered as the sister group of the Saltasauridae.